The Five-substitution Option Enhances Teams’ Running Performance at High Speed in Football - López-Valenciano, Alejandro; Moreno-Perez, Víctor; Campo, Roberto López-Del; Resta, Ricardo; Coso, Juan Del (International Journal of Sports Medicine, 2023)
The aim of this investigation was to describe how the introduction of the five-substitution option affected football teams’ running performance. A comparative analysis was performed in 17 professional football teams for the 2019-2020 (up to three substitutions) vs 2020–2021 (five substitutions option) seasons in LaLiga. The five-substitution option increased the number of substitutions (from 2.9±0.1 to 4.2±1.0 substitutions/match, respectively; p<0.01, Effect Size (ES)=2.11) but it did not change the time selected for the first substitution (from 57.5±13.0 to 56.2±13.7 min; p=0.06, ES=0.1). Total running distance was similar between seasons but running distance at 21.0–23.9 km/h (from 3.0±0.4 to 3.2±0.4 km; p=0.01, ES=0.6) and at≥24.0 km/h (from 3.0±0.6 to 3.2±0.5 km; p=0.01, ES=0.3) were higher with the five-substitution option. These increases were associated with a higher distance covered by starting players (p<0.05) rather than an effect of substitute players. With the five-substitution option, team coaches increased the number of substitutions per match which enhanced the possibilities of the team’s staff to manage players’ physical load. The five-substitution option allowed also increased running performance at≥21.0 km/h during the matches.
Keywords: soccer; injury risk; elite athlete; sprinting